Hedonisme dalam Novel Tokyo dan Perayaan Kesedihan karya Ruth Priscilia Angelina - Sarmita, Devi; Zulfadhli, Zulfadhli (Persona: Kajian Bahasa dan Sastra, 2024)
This research was written to explain the form, causes and impacts of hedonism in the novels Tokyo and Celebration of Sadness by Ruth Priscilia Angelina. This research uses literary research with qualitative research and descriptive methods. The data in this research are words, phrases, clauses or sentences that describe the form, causes and impacts of hedonism in the novels Tokyo and Celebration of Sadness by Ruth Priscilia Angelina using a study of literary psychology theory. The findings of this research include the following forms, causes and impacts of hedonism. (1) Forms of hedonism, namely, (a) natural behavior (innate behavior), (b) operant behavior (operant behavior), (c) egoistic hedonism, (d) universal hedonism. (2) The causes of hedonism consist of internal and external factors. Internal factors are (a) attitude, (b) perception, (c) motive, (d) personality, (e) self-concept. External factors are, (a) family and (b) culture. (3) The impact of hedonism, namely, (a) individualism, (b) materialistic, (c) consumptive, (d) wasteful.